Venous thromboembolism at time of diagnosis of ovarian cancer: Survival differs in symptomatic and asymptomatic cases. (January 2016) - Heath, Owen Mortimer; van Beekhuizen, Heleen J.; Nama, Vivek; Kolomainen, Desiree; Nobbenhuis, Marielle A.E.; Ind, Thomas E.J.; Sohaib, Syed A.; Lofts, Fiona J.; Heenan, Sue; Gore, Martin; Banerjee, Susana; Kaye, Stan B.; et al.
Abstract: Objectives: To determine the impact on survival of symptomatic and asymptomatic venous thromboembolism (VTE) at time of diagnosis of primary ovarian malignancy. Materials and methods: The clinical records of 397 consecutive cases of primary ovarian malignancy were studied. Clinical, pathological and survival data were obtained. Results and conclusions: Of 397 cases, 19 (4.8%) were found to have VTE at diagnosis, of which 63.2% (n = 12) were asymptomatic. VTE was significantly associated with reduced overall median survival (28 vs. 45 months, p = 0.004). Decreased survival was associated with symptomatic VTE compared to patients with asymptomatic VTE (21 vs. 36 months, p = 0.02) whose survival was similar to that of patients without VTE. Decreased survival remained significant in symptomatic patients after controlling for stage of disease at diagnosis, cytoreductive status and adjuvant chemotherapy use. Overall these data suggest for the first time that symptomatic but not asymptomatic VTE prior to primary treatment of ovarian cancer is an independent adverse prognostic factor. Highlights: VTE at the time of diagnosis of ovarian cancer is associated with decreased survival. We show reduced survival in patients with symptomatic but not asymptomatic VTE. Detecting both symptomatic and asymptomatic VTE events is clinically important.